2000
DOI: 10.1086/313911
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Serological Evidence of Bordetella Infections and Mixed Infections with other Respiratory Pathogens in University Students with Cough Illnesses

Abstract: Banked acute-phase and convalescent-phase serum samples from a previous study of respiratory illness in university students were examined for significant (>/=2-fold) increases in ELISA titers of IgA and IgG antibody to Bordetella pertussis filamentous hemagglutinin, pertactin, and fimbriae-2 and >/=4-fold titer increases to agglutinogens by agglutination. ELISA titers of antibody to pertussis toxin could not be determined because of technical problems. Chlamydia pneumoniae infections were diagnosed by culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 31 publications
(45 reference statements)
1
28
0
1
Order By: Relevance
“…During the last two decades, a number of studies have indicated that B. pertussis infections in adolescents and adults are common (55,200,271,354,390,397,534,550,586,634,665,675,695,739,759,788,828,835). There has also been an increase in the number reported cases of pertussis in adolescents and adults in concert with these studies (112,135,199,232,309,702,710,838).…”
Section: B Pertussismentioning
confidence: 96%
See 2 more Smart Citations
“…During the last two decades, a number of studies have indicated that B. pertussis infections in adolescents and adults are common (55,200,271,354,390,397,534,550,586,634,665,675,695,739,759,788,828,835). There has also been an increase in the number reported cases of pertussis in adolescents and adults in concert with these studies (112,135,199,232,309,702,710,838).…”
Section: B Pertussismentioning
confidence: 96%
“…Prolonged cough illness was evaluated in 13 studies published between 1987 and 2002 (Table 7) (55,271,390,397,550,586,665,675,695,739,788,828,835). These studies, in six countries, involved subjects with cough illnesses seen between 1983 and 1999.…”
Section: B Pertussis Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Among adults with cough illness, the incidence of confirmed pertussis has been estimated at 170 to 630 cases per 100,000. 17,18 The rates among adolescents were almost 2-fold higher.…”
mentioning
confidence: 99%
“…B. parapertussis was chosen because at the dose given in this study, infection with B. parapertussis on its own is a subclinical event that causes no apparent illness or weight loss and only minimal inflammation. An Influenza-Bordetella coinfection model also has clinical relevance because this combination is observed in the clinic (36,37). Moreover, the Bordetellae are challenging to culture from biological specimens and difficult to discriminate from other highly similar cocci by traditional microbiological techniques.…”
Section: Discussionmentioning
confidence: 99%